TRANSFORMASI DIGITAL PEMERINTAH DAERAH DI ERA SOCIETY 5.0: STUDI KASUS DI PROVINSI JAWA BARAT - Endang Try Setyasih (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
Society 5.0 relies heavily on the Internet of Things, Big Data, Artificial Intelligence, and Robotics to address a variety of social concerns and issues. The government, particularly local governments, faces the problem of maximizing the use of digital technology to improve public services and governance. Better governance facilitated by digital transformation will not only have an effect on public services, but will also increase citizen involvement and stimulate economic growth. This study examines the local government of West Java province's digital transition towards a digital province in the era of society 5.0. This study employs a qualitative approach and descriptive methodologies. The findings of the study indicate that digital transformation in local government in Indonesia lags behind other nations, particularly those in Southeast Asia. This is due to various constraining factors, including a lack of implementation uniformity, insufficient human resources, inconsistent infrastructure, a lack of community participation, and a lack of government commitment. The regional government of the province of West Java is undergoing a digital transformation, which includes the implementation of the West Java Digital Service (JDS), which includes a digital village as one of its initiatives.